The Effect of Bankruptcy Potential and Corporate Governance Factors on Cash Dividend Policy: The Effect of Bankruptcy Potential and Corporate Governance Factors on Cash Dividend Policy - alyssa risthi (Jurnal Penelitian Ekonomi dan Akuntansi (JPENSI), 2023)
The purpose of this research is to examine the effect of bankruptcy potential and corporate governance factors on cash dividend policy. The corporate governance factor is proxied by the proportion of institutional ownership, managerial ownership, the size of the board of commissioners, the proportion of independent commissioners and the size of the audit committee. The sample selection was carried out using a purposive sampling method, the data is secondary data, the data was obtained from the website of the Indonesia Stock Exchange (IDX) for the period 2017 - 2021. Multiple Linear Regression was used as a method of data analysis and data processing using the eviews 12.0 application. The results of the study show that the potential for financial distress has no effect on cash dividend policy. independent and the size of the audit committee has no significant effect on cash dividend policy